Oil and empire : British policy and Mesopotamian oil, 1900-1920 - Kent, Marian (London : Macmillan, 1976)
Examined the efforts of the British Government to obtain a safeguard oil supplies for the armed forces and the economy.
Based on the author's thesis, London School of Economics and Political Science.
Includes bibliography and index
kjo 16/01/2019
Loans
Keywords: Petroleum industry and trade; Great Britain; Middle East